2011
DOI: 10.1111/j.1469-7610.2011.02420.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic etiology of inhibitory control and behavior problems at 24 months of age

Abstract: Background To investigate links between inhibitory control (IC) and behavior problems in early childhood, as well as genetic and environmental covariance between these two constructs. Methods Parent and laboratory ratings of IC and parent ratings of externalizing and ADHD problem behaviors were administered at 24 months of age on a sample of 291 same-sex twin pairs (131 MZ, 160 DZ). Results There were significant phenotypic associations between both IC assessments and the two areas of behavioral maladjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 50 publications
12
74
0
Order By: Relevance
“…Specifically, high levels of inhibitory control were associated with high levels of reparation via the positive associations of caregiver-reported sympathy and guilt. The primacy of inhibitory control in this mediational chain is in line with recent twin studies documenting a significant genetic component of inhibitory control (Gagne & Saudino, 2010;Gagne et al, 2011). For example, Gagne and Saudino (2010) found that genetic factors accounted for 58% of the variance in caregiver-reported inhibitory control in a sample of 294, 24-month-old twin pairs.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Specifically, high levels of inhibitory control were associated with high levels of reparation via the positive associations of caregiver-reported sympathy and guilt. The primacy of inhibitory control in this mediational chain is in line with recent twin studies documenting a significant genetic component of inhibitory control (Gagne & Saudino, 2010;Gagne et al, 2011). For example, Gagne and Saudino (2010) found that genetic factors accounted for 58% of the variance in caregiver-reported inhibitory control in a sample of 294, 24-month-old twin pairs.…”
Section: Discussionsupporting
confidence: 64%
“…Similar to its hypothesized role in promoting sympathy, inhibitory control may afford children with the regulatory capacity to curb overarousal (e.g., anger and frustration), reflect upon the wrongfulness of their transgression (e.g., feel guilty), and engage in reparation. The primacy of inhibitory control in this theoretical framework has been supported by recent twin studies establishing a significant genetic component of inhibitory control (Gagne & Saudino, 2010;Gagne, Saudino, & Asherson, 2011). Also in line with the present theorizing, recent research has considered the role of sympathy in mediating the effect of temperamental tendencies on prosocial behavior (see Edwards et al, 2014).…”
Section: Inhibitory Control Moral Emotions and Reparative Behaviorsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, for most children, IC emerges late in the second year of life, and develops throughout the toddlerhood and preschool periods (Gagne & Goldsmith, 2011; Gagne & Saudino, 2010; Rothbart, 1989). Understanding IC in early childhood is particularly important because individuals with low IC have more cognitive and socio-emotional development issues such as externalizing behavior problems and associated Attention Deficit Hyperactivity Disorder (ADHD) psychopathology (Eisenberg et al, 2001; 2004; Gagne, Saudino & Asherson, 2011; Schachar, Tannock, Marriott, & Logan, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…One such study of twins demonstrated heritability for these traits, which covaried with externalizing behavior problems and ADHD symptoms [52]. Delay discounting was also shown to be heritable in a longitudinal study of adolescent twins, where this trait was associated with substance use, novelty seeking as well as symptoms of ADHD and conduct disorder [53].…”
Section: Mouse 'Internalizing' Endophenotypes In Drug Discoverymentioning
confidence: 98%